61 Compliance rate in cervical cancer screening among women living with cervical cancer patient in Jose R. Reyes memorial medical center section of gynecologic oncology. (13th November 2020) - Yu, M
Abstract : Background: Cervical cancer is still a leading cause of morbidity and mortality in the Philippines. Despite that it starts from a premalignant to invasive disease and can be prevented by HPV vaccine and monitored by cervical cytology study. This study aims to determine the compliance in cervical cancer screening in women companion of cervical cancer patients. Methods: A descriptive patient survey was undertaken in 42 patients in Gynecologic Oncology Out Patient Department of a tertiary hospital. Women companions were interviewed using the pre-made questionnaire. Results: 42 patients completed the survey. 62% had no cervical cancer screening test and Only 38% had cervical cancer screening test in the form of pap's smear. 44% of which has irregular screening. Lack of time followed by lack of adequate knowledge about cervical cancer screening are the top 2 reasons of non-compliance. However, 83% expressed desire to undergo cervical screening after having a family member or a friend diagnosed with cervical cancer. Conclusions: Being a relative or friend of a cervical cancer patient is not enough to increase the compliance in undergoing cervical cancer screening. It is important to include them in the counseling process and encourage them to undergo screening. This study also recommends a one-stop visit of screening and treatment for the companions of the cervical cancer patient, thus in return reduce the morbidity and mortality of cervical cancer.